2017
DOI: 10.1103/physrevb.96.085437
|View full text |Cite
|
Sign up to set email alerts
|

Energy loss and surface temperature effects in ab initio molecular dynamics simulations: N adsorption on Ag(111) as a case study

Abstract: We study surface temperature effects on the adsorption and relaxation of N atoms on Ag(111). To this aim, we perform ab initio molecular dynamics simulations with electronic friction, in which the surface is coupled to a thermostat that fixes the desired surface temperature. Simulations performed at 80 and 700 K show that the surface temperature has minor effects on magnitudes such as the initial adsorption probability, the relaxation rate of the adsorbing N, and the energy lost in electronic excitations. Slig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…74,114,582 Another topic addressed with DFMDEF is Eley-Rideal reactions, of H-atoms on Cu(111), 583 of D-atoms with CD 3 pre-adsorbed to Cu(111), 584 and of H with Cl preadsorbed to Au (111). 585 Finally, DFMDED calculations investigated scattering of N-atoms from Ag(111), 74,541,582 and dynamic displacement of CO pre-adsorbed to Cu (111) by incident H-atoms. 586 The DFMDEF calculations on vibrational excitation of H 2 on Cu (111) showed that the GLO + LDAF friction method is remarkably accurate in its description of vibrational excitation, at least within the limits of quasi-classical dynamics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…74,114,582 Another topic addressed with DFMDEF is Eley-Rideal reactions, of H-atoms on Cu(111), 583 of D-atoms with CD 3 pre-adsorbed to Cu(111), 584 and of H with Cl preadsorbed to Au (111). 585 Finally, DFMDED calculations investigated scattering of N-atoms from Ag(111), 74,541,582 and dynamic displacement of CO pre-adsorbed to Cu (111) by incident H-atoms. 586 The DFMDEF calculations on vibrational excitation of H 2 on Cu (111) showed that the GLO + LDAF friction method is remarkably accurate in its description of vibrational excitation, at least within the limits of quasi-classical dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…85,136 In principle, reflection of dissipated energy from the bottom of the metal slab modeling the surface may be problematic for non-direct dissociation in a DFMD simulation. If this is suspected, an Andersen thermostat 540 or a Nose ´-Hoover thermostat 541 can be coupled to the atoms in the lower layer of the metal slab to allow for energy dissipation while maintaining the modeled T s in the long term. 93 Of course, with DFMD nuclear motion is treated classically.…”
Section: Dynamical Modelsmentioning
confidence: 99%
“…In the AIMDEF simulations, the forces acting on atom i of HCl (H or Cl) at position r i = ( x i , y i , z i ) T are computed according to 76 …”
Section: Computational Methodologymentioning
confidence: 99%
“…Although Kostov et al showed that CO oxidation cannot be thermally activated under UHV conditions, it has been demonstrated that the reaction can be efficiently propelled by exciting the system with electromagnetic radiation. ,, For instance, both CO and CO 2 are desorbed when the surface is excited using ultraviolet, visible, and near-infrared femtosecond laser pulses. ,, A proper characterization of this kind of experiment requires simulations of the adsorbates dynamics in a highly excited system accurately describing the adsorbate–surface interaction at the DFT level. In particular, the newly developed ab initio molecular dynamics with electronic friction model and its extension to incorporate the effect of a heated electronic system constitutes a promising tool to the study of photoinduced CO oxidation on surfaces.…”
Section: Introductionmentioning
confidence: 99%